Rancang Bangun Sistem Pengeluaran Keuangan di Universitas Catur Insan Cendekia dengan Dynamic Systems Development Method - Dimas Fahreza; Petrus Sokibi; Agung Supriyadi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The development of information technology encourages educational institutions to optimize administrative systems, including financial expenditure management. Currently, Universitas Catur Insan Cendekia does not have a digitalized system to record and manage financial expenditures, resulting in inefficient processes and a higher risk of errors. This research aims to design and develop a web-based financial expenditure application using the Laravel framework with the Dynamic System Development Method (DSDM) as the development approach. DSDM was chosen because it enables a flexible, iterative, and adaptive development process that aligns with user needs. The application provides key features such as expenditure submission, verification, validation, fund disbursement, transaction recording, and financial report generation. The results of this study show that the developed system improves work efficiency, recording accuracy, and transparency in financial management. Therefore, this application is expected to serve as an effective solution to support better financial governance within Universitas Catur Insan Cendekia.